K ustvarjalnosti in inovacijam v vseživljenjskem okolju - Mlinar, Zdravko (Teorija in praksa, 2008)
Awareness about the importance and strivings to stimulate creativity and innovations at all scales are increasing. However, the predominant way of thinking and practices are largely restricted to narrow and out-of-date categories of space, sector, institution, disciplin, social status (hierarchy) and professional frameworks. Creative environment is based on opportunities for integration of diversity. If they are restricted, creativity is restricted as well. The most creative is the environment, which paves the way to the inclusion of all spheres of life (work, residence, recreation, management) and can be denoted as integral living environment. The author points out to the need and possibility for unified treatment of technological innovativeness and cultural-artistic creativity, and for their inclusion into the spatial and urban planning in the time when the zone organization of space is at least in principle overcome. Several open questions and experiences from Koper, Slovenian part of Istria and Primorska are presented.
Keywords: Creativity; Ustvarjalnost; Innovations; Inovacije; Living space; Življenjski prostor; Urban planning; Urbano planiranje; Sociological aspects; Sociološki vidik; Slovenia; Slovenija; prostorska organizacija; labour; delo; bivanje